(untitled) (Analysis in Theory and Applications, 2021)
This paper studies existence of mild solution to a sharp cut off model for contact driven tumor growth. Analysis is based on application of the Crandall-Liggett theorem for ω-quasi-contractive semigroups on the Banach space L^1(Ω). Furthermore, numerical computations are provided which compare the sharp cut off model with the tumor growth model of Perthame, Quirόs, and Vázquez [13].